A Scoping Review on Tangible and Spatial Awareness Interaction Technique in Mobile Augmented Reality-Authoring Tool in Kitchen - Siti Soleha Muhammad Nizam; Meng Chun Lam; Haslina Arshad; Nur Asylah Suwadi (Advances in Multimedia)
The interaction paradigm has changed with the emerging technology, mobile augmented reality, and spatial awareness mobile device. The traditional way for designing a kitchen can cause mistake in measurement and user’s imagination is different from kitchen advisor’s sketch design due to limitation of human imagination. Using mobile augmented reality technology, the user can overlay the virtual kitchen outcome that could fit with the actual kitchen environment. Interaction technique is required in order to allow the user to change the characteristic of the virtual kitchen to suite their need. Thus, this paper is intended to propose the tangible and spatial awareness interaction techniques in the kitchen design authoring tool. A scoping review related to the previous research on tangible and spatial awareness interaction is presented in this paper. The proposed techniques were based on the review on the existing interaction technique and the interview section with the Malaysian kitchen designer by understanding the kitchen design elements and flow. The proposed techniques will be further improved by going through the heuristic evaluation with the augmented reality expert.